MTAP Challenge

Algebra Level 4

9 0 a = 2 , 9 0 b = 5 , 4 5 1 a b 2 2 a = ? \large 90^a = 2, 90^b = 5, 45^{ \frac {1-a-b}{2-2a} } = \ ?

This is a question in MTAP Challenge.

Details and Assumptions

It is 45 45 raised to the power of 1 a b 2 2 a \frac {1-a-b}{2-2a}


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

9 0 a = 2 90^a=2 so 9 0 1 a = 90 9 0 a = 90 2 = 45 90^{1-a}=\dfrac{90}{90^a}=\dfrac{90}{2}=45

Hence:

A = 4 5 1 a b 2 2 a = 9 0 ( 1 a ) 1 a b 2 2 a = 9 0 1 a b 2 = ( 9 0 1 a b ) 1 2 A=45^{\frac{1-a-b}{2-2a}}=90^{(1-a)\frac{1-a-b}{2-2a}}=90^{\frac{1-a-b}{2}}=(90^{1-a-b})^{\frac{1}{2}}

Also:

9 0 1 a b = 90 9 0 a + b = 90 9 0 a × 9 0 b = 90 2 × 5 = 9 90^{1-a-b}=\dfrac{90}{90^{a+b}}=\dfrac{90}{90^a\times 90^b}=\dfrac{90}{2 \times5}=9

Then:

A = 9 1 2 = 3 A=9^{\frac{1}{2}}=3

Taking logs base 45 45 , and letting log \log represent log 45 \log_{45} , we have that

a = log ( 2 ) log ( 90 ) = log ( 2 ) 1 + log ( 2 ) 1 a = 1 1 + log ( 2 ) a = \dfrac{\log(2)}{\log(90)} = \dfrac{\log(2)}{1 + \log(2)} \Longrightarrow 1 - a = \dfrac{1}{1 + \log(2)} .

Also, b = log ( 5 ) 1 + log ( 2 ) . b = \dfrac{\log(5)}{1 + \log(2)}. . Thus

1 a b 2 2 a = 1 log ( 5 ) 2 = log ( 9 ) 2 \dfrac{1 - a - b}{2 - 2a} = \dfrac{1 - \log(5)}{2} = \dfrac{\log(9)}{2} .

we then have that

4 5 1 a b 2 2 a = ( 4 5 log ( 9 ) ) 1 2 = 9 1 2 = 3 45^{\frac{1 - a - b}{2 - 2a}} = (45^{\log(9)})^{\frac{1}{2}} = 9^{\frac{1}{2}} = \boxed{3} .

Same answer as mine :)

Diego Armando Pulido Ramos - 6 years, 4 months ago

Please, how log(2) / log(90) became log (2) / 1 + log(2) ?

Mauro Junior - 6 years, 4 months ago

Since we're working in base 45, we have that

log ( 90 ) = log ( 45 2 ) = log ( 45 ) + log ( 2 ) = 1 + log ( 2 ) . \log(90) = \log(45*2) = \log(45) + \log(2) = 1 + \log(2).

Brian Charlesworth - 6 years, 4 months ago

Thank you!

Mauro Junior - 6 years, 4 months ago

how is log (45)=1 ?

shahzeeb pk - 6 years, 4 months ago

@Shahzeeb Pk Since log \log in this problem stands for log 45 \log_{45} .

For any real a > 0 a \gt 0 we have that log a ( a ) = 1 \log_{a}(a) = 1 , since a 1 = a a^{1} = a .

Brian Charlesworth - 6 years, 4 months ago
Hobart Pao
Feb 21, 2015

I converted 9 0 a = 2 90^{a}=2 to log 90 2 = a \log_{90} 2 = a and and 9 0 b = 5 90^{b} = 5 to log 90 5 = b \log_{90} 5 = b . This becomes a simple substitution problem. Eventually, you get 4 5 1 2 log 45 9 \displaystyle 45^{\frac{1}{2} \log_{45} 9} which is the same as 4 5 log 45 9 1 2 \displaystyle 45^{ \log_{45} 9^{\frac{1}{2}}} and applying the anti log law, you get 3.

Lu Chee Ket
Feb 1, 2015

90 ^(a + b) = 10

a + b = Log 10/ Log 90 = 0.51170721912445836072605926743669

a = Log 2 / Log 90 = 0.15403922195426357566083026916701

45^ 0.28860249407989831592687553274807 = 3

what if a calculator isn't available ?

Izinyon Precious - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...